STRESS-DEFORMED STATE OF A STRUT-FRAMED CRANE GIRDER - Kh. M. Muselemov; O. M. Ustarkhanov; A. K. Yusupov (Вестник Дагестанского государственного технического университета: Технические науки, 2017)
Objectives. The aim of the present work is to study the influence of design parameters on the stress-deformed state of a sprengel crane girder; to compile the tables and corresponding graphs illustrating changes in internal force factors in the characteristic cross-sections of the system elements under consideration. The article describes the study of the stress-deformed state (SDS) of a metal strut-framed crane girder.Methods. Numerical methods of analysis based on the use of the Green's function are used during solving this problem. A dimensionless parameter is introduced, depending on which the tables and graphs are constructed. According to the known algorithm, the calculations of internal force factors in the sections of the considered construction are performed.Results. Depending on the dimensionless parameter characterising the geometry and physical features of the system, tables of bending moments and transverse forces are compiled. According to these tables, the appropriate graphs are plotted in order to choose easily the optimal design parameters.Conclusion. The dependence of the moments and transverse forces on the dimensionless parameter k was found, the corresponding graphs were plotted and the metal costs for the girders were calculated. The minimum values of the moments and transverse forces are established to take place when the dimensionless parameter k values are close to zero. The most economical was a strut-framed crane girder having k = 0.0001. The most uneconomical had k = 0.05 and k =∞. Eventually, the sprengel girders were found to be more profitable as compared to conventional crane girders. In the examples considered in the article, the metal savings amounted up to 14%. The presented methodology allows the calculation and designing of strut-framed crane girders with two racks to be carried out.